2D/2D Heterojunction of TiO2 Nanoparticles and Ultrathin G-C3N4 Nanosheets for Efficient Photocatalytic Hydrogen Evolution - Du, Ruifeng; Li, Baoying; Han, Xu; Xiao, Ke; Wang, Xiang; Zhang, Chaoqi; Arbiol, Jordi; Cabot, Andreu (Nanomaterials (Basel, Switzerland), 2022)
Photocatalytic hydrogen evolution is considered one of the promising routes to solve the energy and environmental crises. However, developing efficient and low-cost photocatalysts remains an unsolved challenge. In this work, ultrathin 2D g-C3N4 nanosheets are coupled with flat TiO2 nanoparticles as face-to-face 2D/2D heterojunction photocatalysts through a simple electrostatic self-assembly method. Compared with g-C3N4 and pure TiO2 nanosheets, 2D/2D TiO2/g-C3N4 heterojunctions exhibit effective charge separation and transport properties that translate into outstanding photocatalytic performances. With the optimized heterostructure composition, stable hydrogen evolution activities are threefold and fourfold higher than those of pure TiO2, and g-C3N4 are consistently obtained. Benefiting from the favorable 2D/2D heterojunction structure, the TiO2/g-C3N4 photocatalyst yields H2 evolution rates up to 3875 μmol·g−1·h−1 with an AQE of 7.16% at 380 nm.